Digital centralized water meter using 433 MHz LoRa - Hudiono Hudiono; Mochammad Taufik; Ridho Hendra Yoga Perdana; Amalia Eka Rakhmania (Institute of Advanced Engineering and Science, 2021)
The local water supply corporation in Indonesia only uses analog water meter so that the monitoring of water usage information was conducted by officers manually. Officers must physically monitor the value in the customer's water meter that can lead to unreliable reading and ineffectiveness of process. Smart meter is one of the smart city metrics which could overcome this problem. This research uses the flow sensor to design and incorporate automated water meters. The measured value is then passed via the 433 MHz LoRa, a low-power wide-area network protocol, to the local hub, then forwarded to the server via the internet based cellular network. Results show that our proposed system's accuracy hit 97.31% at an ideal distance of 200 meters from customer to the local hub. The customer's water usage could be tracked in real time with our proposed system. Furthermore, the original water meter need not to be replaced which may minimize capital costs for this system.